2016
DOI: 10.1007/978-3-319-31235-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategies for Developing Reading Comprehension

Abstract: This chapter focuses on instructional strategies for improving reading comprehension of students with learning disabilities (LD). It discusses the nature of reading comprehension and highlights comprehension diffi culties experienced by students with LD. This discussion is followed by a selective overview of the research on cognitive and metacognitive strategies, with a focus on components of effective instruction gleaned from the research on reading comprehension. Keywords Reading comprehension • Reading stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Some authors support the position that there is an association between contextual knowledge and the comprehension skills of EHL (Gajria & Jitendra 2016;Kendeou & O'Brien 2018). In this study, the teachers' responses gave a clear picture of the positive impact of the activities, which they engaged their learners in, as making a major contribution.…”
Section: Discussion Of Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors support the position that there is an association between contextual knowledge and the comprehension skills of EHL (Gajria & Jitendra 2016;Kendeou & O'Brien 2018). In this study, the teachers' responses gave a clear picture of the positive impact of the activities, which they engaged their learners in, as making a major contribution.…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…In this study, the teachers' responses gave a clear picture of the positive impact of the activities, which they engaged their learners in, as making a major contribution. Furthermore, it was acknowledged that the technique of incorporating context knowledge using games, puzzles and songs while teaching words helped adapt the teaching style to the comprehension skills of EHL -especially with respect to learners from diverse language backgrounds (Gajria & Jitendra 2016;Kendeou & O'Brien 2018). Participants alluded to the fact that music was also a powerful way to influence school learners' emotional behaviour, as they saw singing as a calming game or practice, not as an educational process.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Furthermore, in Flanders (Belgium), the present study's context, there is a decreasing trend in diagnosing learning disabilities, and in particular diagnosing dyslexia, as this certificate is no longer a prerequisite to receive supplementary educational support (Ghesquière, 2014). Previous research has found that struggling readers lack appropriate and consistent reading comprehension strategies, a factor correlating with effective reading comprehension (Gajria & Jitendra, 2016). Additionally, due to frequent reading failure experiences, struggling readers often show low reading motivation, which is also correlated with effective comprehension (Gambrell et al, 2018;Vaknin-Nusbaum et al, 2018).…”
Section: Struggling Readersmentioning
confidence: 99%
“…In addition, metacognitive strategies enable readers to participate actively in the reading process by developing critical thinking skills (Hong-Nam et al, 2014;Sencibaugh, 2007). These skills help readers to evaluate the effectiveness of the reading strategy they use and make changes when they detect a problem in understanding (Gajria, & Jitendra, 2016). However, insufficiency of metacognitive strategy knowledge can prevent students from realizing misunderstandings in the reading process (Michalsky et al, 2009).…”
Section: Metacognitive Strategies and Reading Achievementmentioning
confidence: 99%